Perinatal maternal alcohol consumption and methylation of the dopamine receptor DRD4 in the offspring: the Triple B study - Fransquet, P.; Hutchinson, D.; Olsson, C.; Wilson, J.; Allsop, Steve; Najman, J.; Elliott, Elizabeth; Mattick, R.; Saffery, R.; Ryan, J. (2016)
Maternal alcohol use during the perinatal period is a major public health issue, the higher ends of which are associated with foetal alcohol spectrum disorder and a range of adverse health outcomes in the progeny. The underlying molecular mechanisms remain largely unknown but may include the epigenetic disruption of gene activity during development. Alcohol directly activates the neurotransmitter dopamine, which plays an essential role in neurodevelopment. To investigate whether antenatal and early postnatal alcohol consumption were associated with differential dopamine receptor DRD4 promoter methylation in infants (n = 844). Data were drawn from the large population based Triple B pregnancy cohort study, with detailed information on maternal alcohol consumption in each trimester of pregnancy and early postpartum. DNA was extracted from infant buccal swabs collected at 8-weeks. DRD4 promoter DNA methylation was analysed by Sequenom MassARRAY. No strong evidence was found for an association between alcohol consumption during pregnancy and infant DRD4 methylation at 8-weeks postpartum. However, maternal alcohol consumption assessed contemporaneously at 8-weeks postpartum was associated with increased methylation at 13 of 19 CpG units examined (largest Δ + 3.20%, 95%Confidence Interval:1.66,4.75%, P =  0.0001 at CpG.6). This association was strongest in women who breastfeed, suggesting the possibility of a direct effect of alcohol exposure via breast milk. The findings of this study could influence public health guidelines around alcohol consumption for breastfeeding mothers; however, further research is required to confirm these novel findings.